Trade Facilitation in Developing Countries: Can Blockchain Prompt a Leap Forward? - United Nations Conference on Trade; Development (United Nations, 2020)
The entry into force of the Agreement on Trade Facilitation of the World Trade Organization in February 2017 propelled the concept of trade facilitation into mainstream policy dialogue and brought major attention to the challenges traders face, particularly in developing countries. At the same time, e-commerce (electronic commerce), just-in-time delivery, global value chains and smart shipping have been on the rise. Crossborder business-to-business, business-to-consumer and even consumer-to-consumer e-commerce, for instance, is poised to become globally ubiquitous, bringing along with it challenges for Governments. The challenges involve the implications for compliance, revenue collection, consumer protection, competition policy and safety and security. Amid these developments, how can Governments keep trade risks low and, at the same time, facilitate cross-border trade? Can modern technologies, such as blockchain, provide a solution and allow developing countries to make leaps forward in efficiency?